O material didático para o ensino de Português como Língua de Acolhimento (PLAc): construindo critérios de avaliação - Paula, Daniele Pechi de [UNIFESP] (2023)
The context of this dissertation is the teaching of Portuguese as a Host Language in Brazil. This dissertation discusses the specificities involved in creating and assessing didactic materials for this specific purpose. The objectives of this investigation are to report the history and contexts of creating the Pode Entrar textbooks and the Portas Abertas and Vamos Juntos(as)! Collections, describing the books’ linguistic ideologies present in these books and the profile of the suggested activities, and propose analysis criteria for Portuguese as a Host Language didactic materials that were tested on analyses made by teaching units in this investigation’s corpus. This is a work that used documentary research to survey the PLAc teaching materials that have already been published in Brazil, qualitative research, through in-depth interviews with authors of the analyzed textbooks and bibliographical research for investigating criteria for assessment of didactic materials for teaching additional languages. From an epistemological point of view, this dissertation falls within the domain of Applied Linguistics, more specifically the one that understands the field from an indisciplinary perspective (MOITA LOPES, 2018) mobilizing theoretical resources that contribute to reflect about the specific research problem presented in this investigation. Based on the debates held by several authors on the concept of Portuguese as Host Language (GROSSO, 2010, CABETE 2010, OLIVEIRA & GOMES, 2014, LOPEZ, 2018, ANUNCIAÇÃO 2018, RUANO, 2019, DINIZ and SCARAMUCCI, 2022, among others) on language policies and language ideologies (RICENTO and HORNBERGER 1996, BLOMMAERT, 2003, HORNBERGER and JOHNSON 2007, DINIZ 2012, BIZON and CAMARGO, 2018, ANUNCIAÇÃO, CAMARGO and LOPEZ, 2021, among others), about culture and transculturality in language education (MENDES 2004 and 2012, MAHER 2007, SALOMÃO 2015, among others) and about the functions and criteria to evaluate didactic materials (OLIVEIRA and FURTOSO, 2009, DINIZ, STRADIOTTI and SCARAMUCCI, 2009, SCHEYERL, 2012, MENDES 2012, TILIO 2016, BIZON and DINIZ, 2019, among others), I tried to understand the ways in which Portuguese as Host Language teaching materials are being constructed and present criteria to analyze them. Seeking to describe which are the conceptions of language and culture in the didactic materials and the representation of the students, I tried to answer in the first chapter of analysis what the context of production of Portuguese as Host Language textbooks reveal about how the linguistic reception of crisis migrants is done in Brazil and how such publications represent their target group. Then, in the second analysis chapter, based on the evaluation criteria of additional language textbooks selected for this research: graphic design, teacher's manual, nature of the activities, critical multilingualism (TILIO, 2016), and interculturality, I evaluated two didactic units of each book. The analysis of this corpus showed that the thematic choices are very similar and significant for the migrant public, however, the operationalization of activities and work with genres, in order to promote critical literacy (JORDÃO, 2016) could be better developed in two of the three publications analyzed. The results point to a language teaching that would need to take more the students' linguistic and cultural repertoires into consideration in two out of the three publications analyzed, and the need of developing a transcultural approach for teaching Portuguese as a Host Language that allows students to transition between languages, develop autonomy and enfranchisement, and have their rights as de facto citizens ensured and respected.